The impacts of social media on investment behaviour in Malaysia - Chin, Ji Yan; Sia, Elsie; Lim, Eu Jun; Lin, Zhi Yao (2024)
The primary objective of this study is to determine the factors that influence social media investment behavior in Malaysia. The four independent variables are information reliability, company image, online community behavior, and the overall aspect of social media, whereas the dependent variable is Malaysian investment behavior. The information and information needed for this study was acquired utilizing a survey questionnaire that was administered by us methodology with Google Forms, which is a primary research methodology. Only 407 of the 483 surveys gathered were judged appropriate for use following a screening process. We utilized Statistical Product and Service Solutions (SPSS)27.0 software to analyze our data. In this study, the data were analyzed using many methods, including the test for reliability, normality test, multicollinearity, and multiple linear regression. The findings indicate that information reliability, firm image, and online community behavior all have a substantial influence on investment behavior in Malaysia, however, the overall aspect of social media has no significant impacts on the investment behavior in Malaysia. Our study findings have significant consequences for academia, industry, stakeholders, and policy. We also make recommendations that are for future researchers to perform more exact and accurate studies regarding this area, therefore addressing the limitations of our work.